Effect of pilot-scale high-temperature short-time processing on the retention of key micronutrients in a fortified almond-based beverage: implications for fortification of plant-based milk alternatives - Redan, Benjamin W.; Zuklic, Joseph; Cai, Jiarui; Warren, Joshua; Carter, Coleton; Wan, Jason; Sandhu, Amandeep K.; Black, Darryl Glenn; Jackson, Lauren S. (Frontiers in Nutrition, 2024)
The effect of thermal processing treatments on key micronutrients in fortified almond-based beverages has not been well characterized. An almond-based beverage was produced in a pilot plant, fortified with vitamin A palmitate, vitamin D2, riboflavin (vitamin B2), calcium carbonate, and zinc gluconate, and was processed using various high-temperature short-time (HTST) pasteurization treatments. Naturally present micronutrients in the base ingredients included several B vitamins (vitamin B1 [thiamin], total vitamin B3 [sum of nicotinamide and nicotinic acid], and total vitamin B6 [sum of pyridoxal, pyridoxamine, and pyridoxine]) and minerals (magnesium, phosphorus, and potassium). The prepared almond-based beverage was homogenized and thermally processed using HTST pasteurization with a temperature range from approximately 94 to 116 °C for a constant time of 30 s. The samples were analyzed for vitamin A palmitate, vitamin D2, target B vitamins (thiamin, riboflavin, total vitamin B3, and total vitamin B6), and minerals (magnesium, phosphorus, potassium, calcium, and zinc). The results showed that amounts of vitamin A, vitamin D2, riboflavin, and total vitamin B6 did not significantly (p>0.05) change after the HTST treatments, whereas thiamin significantly (p<0.05) decreased by 17.9% after HTST treatment at 116 °C. Interestingly, total vitamin B3 content significantly (p<0.05) increased by 35.2% after HTST treatment at 116 °C. There was no effect of processing on the minerals that were monitored. The results from this study indicate that the majority of key micronutrients assessed in this study are stable during HTST processing of an almond-based beverage and that fortification of plant-based milk alternatives may be a viable process to enhance the micronutrient content consumers receive from these products.